Rabbit dietary supplementation with pale purple coneflower. 2. Effects on the performances, bacterial community, blood parameters and immunity of growing rabbits. (14th January 2016) - Kovitvadhi, A.; Gai, F.; Dabbou, S.; Ferrocino, I.; Rotolo, L.; Falzone, M.; Vignolini, C.; Gennero, M. S.; Bergagna, S.; Dezzutto, Daniela; Barbero, R.; Nebbia, P.; et al.
Abstract : Echinacea pallida (EPAL), a herbaceous flowering plant with immunomodulatory properties, has been chosen to determine the pre- and post-supplementary effects on the growth performances, bacterial community, blood parameters and immunity of growing rabbits. The same Grimaud does (14-week-old) from the studied in the first part of this study were randomly divided into two groups ( n =50/group). The first group was fed a basal diet without supplementation (Control group, C) while the another group was fed a basal diet supplemented with 3 g EPAL/kg diet ( Echinacea group, E). From the second parturition, 80 weaned kits (40 from the C does and 40 from the E does) were randomly assigned to four groups of 20 animals each and were fed a growing commercial diet supplemented with or without a 3 g EPAL/kg diet: the CC group (rabbits from the C does fed the control diet), CE group (rabbits from the C does fed the supplemented diet), EC (rabbits from the E does fed the control diet) and EE group (rabbits from the E does fed the supplemented diet). The dietary EPAL treatment did not affect the growth performance. Ten fattening rabbits from each group were selected to evaluate the bacterial community and blood parameters, while the remaining rabbits ( n =10/group) were used to study phagocytosis and the humoral immune response. The variability was evaluated from hard faeces at 35, 49 and 89 days, and the caecal content at 89 days. The variability of the bacterial community of the EE group was higher than that of the other groups. The phagocytic activity was higher in the CE and EE groups than in the CC and EC ones (30.9 and 29.7 v . 21.2 and 21.8%; P <0.05), whereas no statistically significant difference was observed for the blood parameters or humoral immune response against vaccination (rabbit haemorrhagic disease virus) at 95 days old which the serum was collected at 88, 102, 109, 116 and 123 days old. In conclusion, no impact of EPAL dietary supplementation has been observed on the growth performances, bacterial community, blood parameters or humoral immune responses in growing rabbits, except for an increase in phagocytic activities.